ANALYSIS OF FACTORS AFFECTING VIRTUAL TEAMS PERFORMANCE ON BUSINESS PROJECTS - Wijaya, Justin; Mustikarini, Carolina Novi; Rahman, Fajar Adzani (International Business Management - Universitas Ciputra, 2023)
Current technological developments help people to transform learning in a new era to build creativity, hone skills, and improve self-quality by changing the systems, perspectives, and patterns of community interaction with technology, one of which is virtual teams. The interaction of virtual teams has become a way to run a business for organizations can survive in a globally competitive environment. Therefore, organizations need to understand what makes virtual teams more effective and get positive results from virtual teams. The object of this research is the businesses run by students engaged in various sectors who do virtual teams in running their businesses. This research aims to determine the factors that affect the virtual team’s performance. This research is quantitative research with the population of Ciputra University students majoring in the International Business Management Study Program – Regular Class (IBM-RC) who is running a virtual team. Data was gathered using online questionnaires, and then a Confirmatory Factor Analysis (CFA) test was used to confirm the components found in the research variables. The results of the study show that coordination, communication, relationship building, cohesion, trust, and reward are factors that affect the virtual team’s performance.